Social support for caregivers of children with Down’s Syndrome - Rezende, Luciana Krauss (2014)
The objective of this study was to know the perception of social support for caregivers of children with Down’s syndrome (DS) in relation to the degree of satisfaction and the number of people to support in the southern region of the State of Minas Gerais and establish the relationship between them. This is a study of quantitative analysis, exploratory and descriptive character, and clinical type cross-section. The study population consisted of 50 people from both genres, mostly mothers (92), caregivers of children with DS, aged 6 months and 7 and a half years, regular goers of specialized agencies. To the group studied, the vast majority of responses indicating supportive people pointed out the lack of a reference person, being ticked the answer "no". Then appear the husband, son, parents, siblings, friends, wife and children's doctor. The analysis of the correlation between the number of supportive people and satisfaction with social support showed satisfaction among low and moderate denoting that these caregivers could not count on a network of efficient social support in caring for children with DS. It is considered appropriate to increase actions and governmental and non-governmental incentives for the development of professional teams and specialized institutions focused care, rehabilitation and inclusion of children with DS and their families into society. Families need appropriate support programs in order to foster their capabilities.